SISTEM AKUNTANSI PENGGAJIAN PADA KOPERASI KARYAWAN YAYASAN ANAKKU - Rully Movizar (Jurnal Ekonomi dan Manajemen, 2023)
All business organizations, including non-profit organizations, need an accounting system. The resulting financial information can be used as an accountability from one party to another. A good accounting system will be able to provide financial information that is needed by interested parties in assessing the performance of an entity and can then determine attitudes for decision making. A good accounting system must apply systematic internal control. If there are components of internal control that are lacking or not implemented, then it could be that the implementation of the accounting system in an entity will run less than optimally. -functions that should be and also to provide suggestions or recommendations regarding the best payroll accounting system for the Anakku Foundation Employee Cooperative. The data used in this study are in the form of interview results and also the required documents such as written notes to related letters. From the data analysis it can be seen that the payroll accounting system at the Anakku Foundation Cooperative has been running well because it is in accordance with the internal control structure, but there are still weaknesses, namely the lack of supervision of recording the time of attendance of the Anakku Foundation Employee Cooperative employees.